(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
A facile strategy for obtaining Polyaniline (PANI) composites was reported wherein the reaction is oxidation polymerization using Dodecylbenzene Sulfonic Acid (DBSA) as the initiator, Polyvinyl Alcohol (PVA) as the emulsifier, and the Ammonium Peroxydisulfate (APS) as the oxidizing agent. The structure and performance of PANI composites were investigated. The results indicated that PANI particles can be dispersed evenly in the PVA matrix, the conductivity and electrochemical properties of the PANI/PVA composites were affected by the protonic acid content, When n(DBSA)/n(AN) = 1.0 under the same condition, the conductivity of PANI membrane is up to 1.28 S/cm. From the FTIR spectrum, the characteristic peaks of PANI at 1459 cm^-1 and 1697 cm^-1 are attributed to the C = C stretching vibration peak of the quinone ring and the benzene ring and the C = N stretching vibration peak of the quinone ring. The asymmetric ECD of PANI/PVA composites with copper and silver fabrics have both three brilliant colors (green - blue - yellow primary colors).